Scientific Biographies of Women. A Few Remarks on Whether and How to Research Them? - Kolbuszewska, Jolanta (Sensus Historiae, 2021)
The purpose of this article is to reflect on validity and need for research into the scientific careers and academic advancement of women. The author thinks about the goals and methods of this type of research. In reference to three recently published monographs (presenting the scientific profile of Wanda Moszczeńska, prosopographical research on the milieu of Polish female historians and an attempt to present the history of the university from the perspective of women), she presents various approaches to the subject.